Chicano/a Mural with Aztec Iconography in Estrada Courts - Felix, Charles
Charles Felix (Cat) B.1944 - D.1990 - Red and green depiction of an ancient stone relief from El Tajin, the ancient capital of a civilization near present-day Veracruz, Mexico.